Littoral cell angioma of the spleen in a patient after treatment of laryngeal cancer and colonic adenocarcinoma – case report and review - Murawa, Dawid; Nowaczyk, Piotr; Kurzawa, Paweł (Contemporary Oncology/Współczesna Onkologia, 2008)
The aim of this study is to report a case of littoral cell angioma of the spleen (LCA), a rare vascular splenic neoplasm. The patient, aged 74, was admitted to the 1st Clinic of Surgical Oncology and General Surgery, Great Poland Cancer Centre, on January 2008 with the suspicion of splenic lymphoma or splenic metastases (abdominal CT). He underwent partial laryngectomy in 2004 (laryngeal cancer) and transversectomy in 2007 (colonic adenocarcinoma). Splenectomy was conducted. Final diagnosis – LCA. The patient made an uneventful recovery. Last follow-up on April 2008 – no sign of neoplastic disease. LCA has intermediate features between those of endothelial and histiocytic cells. Pathogenesis is connected with dysregulation of the immune system resulting in occurrence of LCA together with malignant tumours. Clinically, patients present with hypersplenism, fever, abdominal pain and fatigue. Neoplasm appears as multiple lesions in abdominal US, CT, MRI or Tc99m RBC scans. The treatment is splenectomy. With regard to pathogenetic conditioning close clinical follow- -up is recommended. LCA is a benign tumour, but it is important to differentiate it from malignant vascular neoplasm, splenic lymphomas or metastases.